Quality of Life, Perceived Social Support and Death Anxiety Among People Having Cardiovascular Disorders: A Cross-Sectional Study - Muhammad Hashim, Waqar Azim, Wajid Hussain, Fazal Ur Rehman, Abdul Salam, Muhammad Rafique, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the quality of life, perceived social support, and death anxiety among people having cardiovascular disorders Study type: A Cross-sectional study Place and Duration: This study was conducted at Civil Hospital, BMCH Quetta Pakistan from June 2020 to June 2021 Methodology: This study was designed to evaluate the correlation between quality of life, hope, and death anxiety among people having cardiovascular disorders. We gathered data by using a convenience sampling technique for 4 months. We used the questionnaire method for our survey. Our questionnaire was based on five sections including basic demographic, the 17-item McGill QoL (MQoL) Questionnaire, Herth hope to score, Thorson-Powell Death Anxiety Scale (TPDAS), and Death depression scale (DDS). Results: Out of 500 participants half of them were female (52.4%), most of the participants were married with no formal education and belonged to poor or middle-class families. Participants with intermediate education levels who were financially dependent on the government had a better quality of life than others. We observed that patients with myocardial infarction (MI) had higher levels of anxiety. Furthermore, we observed that patients with a belief in life after death had higher death anxiety than those who don't believe. Conclusion: Our results concluded a positive association among quality of life and hope. We examined that social support plays a vital role in managing CVD disorders. However, patients with myocardial infarction had high levels of death anxiety than others.